Between Art, Industry and Entrepreneurship: Artistic, Design, and Managerial Activity of Professor Zbigniew Horbowy in 1959–1989 - Popiński, Krzysztof (Studia Historiae Oeconomicae, 2022)
Zbigniew Horbowy (1935–2019), a graduate of the Faculty of Glass of the State Higher School of Fine Arts in Wrocław, conducted from the end of the 1950s, throughout the next several decades, exceptionally fruitful and original artistic, academic, design and managerial activities on the intersection of art and industry. His artistic achievements quickly found recognition in the national art circles and in the international arena. At the same time, as the only glass designer in the times of the Polish People’s Republic, he managed to combine artistic and commercial success. The utility glasses designed by him and mass-produced and sold on a mass scale were a symbol of Polish glass in general in the public awareness. He carried out his entrepreneurial activity with amazing efficiency in spite of the conditions of the industry in the People’s Republic of Poland. And this, in principle, was extremely difficult to effectively use innovation or design. As a lecturer at the PWSSP (State Higher School of Fine Arts), then a member of the university’s management and at the same time the head of design units of the leading Lower Silesian glassworks, he played an extremely important role in educating design staff and development directions of Polish industrial design.